Estudio de las alteraciones histopatológicas en cerdos infectados experimentalmente con Trichinella spiralis - Ribicich, M. (2004)
Trichinellosis is a zoonotic disease and the cycle between pig/man is an important tool in the epidemiology. The housing in the skeletal muscles of the nematode Trichinella spiralis and the passage of the new born larvae through the body, produce deep pathologic changes in different organs and tissues. In this work we have studied the histopathological changes produced by larvae migration in 14 pigs that were orally inoculated with 100, 500, 5000 and 50.000 infective larvaes of T.spiralis. Pigs were killed at 100 days post-inoculation and muscular tissues and organs were analized by histopathology. Samples of heart, lung, kidney, liver, spleen, lymph nodes, and muscles of tongue, tongue base, masseters, intercostals, shoulder, sublumbar, neck, cutaneous, of lateral of thigh and diaphragm were obtained. Results described the predilection site selected by larvaes during the migration phase and the pathological changes produced by that in different organs and muscles of pigs.